2008
DOI: 10.1128/jvi.02148-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alveolar Macrophages in Respiratory Transmission of Visna/Maedi Virus

Abstract: A major route of transmission of Visna/maedi virus (VMV), an ovine lentivirus, is thought to be via the respiratory tract, by inhalation of either cell-free or cell-associated virus. In previous studies, we have shown that infection via the lower respiratory tract is much more efficient than via upper respiratory tissues (T. N. In this study, we use an experimental in vivo infection model that allowed the infection of specific segments of the ovine lung. We demonstrate that resident AMs are capable of VMV upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 42 publications
0
36
0
4
Order By: Relevance
“…Their results indicated that the LTR determined the extended cell tropism of the MVV. Therefore, in live animals, virus isolation can be conducted on peripheral blood, milk and inhalation of infected alveolar macrophages (Christodoulopoulos 2006;Gil et al 2006;McNeilly et al 2008;Barquero et al 2011). At necropsy, MVV can be isolated from the lungs, mediastinal lymph nodes, spleen, third eyelids and kidneys of affected animals (Capucchio et al 2003;Angelopoulou et al 2006;Benavides et al 2006;Laamanen et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Their results indicated that the LTR determined the extended cell tropism of the MVV. Therefore, in live animals, virus isolation can be conducted on peripheral blood, milk and inhalation of infected alveolar macrophages (Christodoulopoulos 2006;Gil et al 2006;McNeilly et al 2008;Barquero et al 2011). At necropsy, MVV can be isolated from the lungs, mediastinal lymph nodes, spleen, third eyelids and kidneys of affected animals (Capucchio et al 2003;Angelopoulou et al 2006;Benavides et al 2006;Laamanen et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The highest BFV DNA load was observed in lungs, liver, and spleen of experimentally inoculated calves at the early phase p.i., while in long-term-infected sheep and naturally infected cows, much lower overall DNA loads were detected. Detection of FV DNA in a particular tissue does not necessarily indicate active virus replication since alveolar macrophages and areas of lymphocyte aggregation or lymphoid proliferation are known to act as latent reservoirs of other retroviruses like Maedi-Visna virus or human immunodeficiency virus (HIV) (54,55,56,57). Furthermore, since lymphocytes have been previously identified as targets of FV infection (58), the presence of viral DNA in lungs can be explained by BFV-infected lymphocyte and monocyte-derived macrophage infiltration or by high vascularization and an enrichment of infected leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…27,77,83 Both cell-associated and cell-free OPPV and VISNA have been found in colostrum, milk, and bronchial alveolar lavage (BAL) fluid of the lung of serologically positive ewes. 10,39,52,53,56,57 The OPPV or VISNA in the BAL fluid is thought to be the major source of horizontal transmission in sheep; however, there have not been any reports demonstrating the shedding of OPPV, VISNA, or CAEV in oronasal secretions. Interestingly, although cell-associated OPPV, found in the colostrum or milk of 6-year-old, lactating ewes, in both meat and wool breeds, and transmitted to lambs, establishment of persistent infection based on the presence of peripheral provirus load and OPPV serum antibodies only occurred in 5% of lambs (1 of 22) during 6 years of surveillance (LM HerrmannHoesing, unpublished data, 2008).…”
Section: Transmission Sourcesmentioning
confidence: 99%